2007
DOI: 10.1104/pp.107.098731
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Lack of Phosphatidylglycerol on the Donor Side of Photosystem II

Abstract: Our previous studies with the pgsA mutant of the cyanobacterium Synechocystis sp. PCC6803 (hereafter termed pgsA mutant), which is defective for the biosynthesis of phosphatidylglycerol (PG), revealed an important role for PG in the electron acceptor side of photosystem II (PSII), especially in the electron transport between plastoquinones Q A and Q B . This study now shows that PG also plays an important role in the electron donor side of PSII, namely, the oxygen-evolving system. Analyses of purified PSII com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
52
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 53 publications
(65 reference statements)
5
52
0
Order By: Relevance
“…It was also found that photosynthetic oxygen-evolving activity of dgdA mutant cells was decreased by heat treatment (Fig. 6), which is similar to our previous finding that inactivation of oxygen evolution was induced in PG-depleted pgsA mutant cells (Sakurai et al, 2007). In the PG-depleted pgsA mutant cells, inactivation of oxygen evolution was also observed during dark incubation as in the DpsbO and DpsbV mutant cells (Sakurai et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was also found that photosynthetic oxygen-evolving activity of dgdA mutant cells was decreased by heat treatment (Fig. 6), which is similar to our previous finding that inactivation of oxygen evolution was induced in PG-depleted pgsA mutant cells (Sakurai et al, 2007). In the PG-depleted pgsA mutant cells, inactivation of oxygen evolution was also observed during dark incubation as in the DpsbO and DpsbV mutant cells (Sakurai et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…The cdsA mutant had phenotypes similar to the pgsA mutant. Through detailed analyses of the pgsA mutant, we demonstrated an important role of PG in the acceptor side of PSII at the Q B site (Gombos et al, 2002;Sakurai et al, 2006) as well as in the donor side of PSII for the binding of extrinsic proteins required for sustaining the manganese (Mn) cluster (Sakurai et al, 2007).…”
mentioning
confidence: 99%
“…The results indicate that CS-73 is slightly more sensitive to heat stress-induced inactivation of PSII in the dark than OTcH-1. In cyanobacteria Synechocystis PCC6803 (27)(28)(29) and green alga Chlamydomonas reinhardtii (30), different lipid composition of the thylakoid membranes has been demonstrated to correlate with the thermal stability of PSII at the oxygen production site.…”
Section: Resultsmentioning
confidence: 99%
“…PG plays an important role in the oligomerization of the light harvesting complex and the dimerization of PSII (McCourt et al, 1985;Krupa et al, 1987;Kruse et al, 2000). It is also required for both the electron-acceptor side and the donor side of PSII (Sakurai et al, 2007). The DBI was increased by drought stress, but decreased by UV-B radiation in leaf PE.…”
Section: Discussionmentioning
confidence: 99%